Natal Teeth: A Case Report and Reappraisal - Ghadah A. Malki; Emad A. Al-Badawi; Mohammad A. Dahlan (Case Reports in Dentistry)
The presence of teeth at birth (natal teeth) or within a month after delivery (neonatal teeth) is a rare condition. Natal and neonatal teeth are conditions of significant importance to pediatric dentists and pediatricians. This report discusses a case in which a five-day-old infant required extraction of a mobile mandibular natal tooth to avoid the risk of aspiration and interference with feeding. Also, a review of the literature was conducted to discuss the etiology, clinical features, complications, and management of natal and neonatal teeth.